Kewirausahaan Islam di Selatan Thailand: Integrasi Etika Islam, Koperasi Syariah, dan Literasi Keuangan dalam Penguatan Ekonomi Umat - Bado, Abdunmumin; Indrawijaya, Sigit; Zamzami, Zamzami (Journal of Business Studies and Management Review, 2025)
This article examines the dynamics of Islamic entrepreneurship in Southern Thailand, particularly in the provinces of Pattani, Yala, and Narathiwat, which are predominantly inhabited by Malay Muslims. This study employs a qualitative descriptive method through a literature review approach, integrating findings on the business practices of Muslim entrepreneurs, the role of Islamic cooperatives, Islamic financial literacy, and community access to halal financing. The results indicate that while the community demonstrates a strong commitment to conducting business in accordance with Islamic principles, Islamic entrepreneurship in the region faces several structural challenges. These include a limited understanding of Islamic jurisprudence (Fiqh Muamalah), low levels of Islamic financial literacy, restricted access to formal Islamic financial institutions, and external economic shocks such as the COVID-19 pandemic. However, the existence of the Pattani Islamic Cooperative, community-based business initiatives, and the optimization of Islamic social finance instruments such as zakat, waqf, and sadaqah provide significant opportunities to strengthen the ecosystem. This article concludes that the sustainable development of Islamic entrepreneurship in Southern Thailand requires a strategic integration of ethical reinforcement, institutional support from cooperatives, and enhanced financial literacy.